Conformational cooling and conformation selective aggregation in dimethyl sulfite isolated in solid rare gases - Borba, Ana (2006)
Dimethyl sulfite has three conformers of low energy, GG, GT and GG0, which have significant populations in the gas phase at room temperature. According to theoretical predictions, the GT and GG0 conformers are higher in energy than the GG conformer by 0.83 and 1.18 kJ molK1, respectively, while the barriers associated with the GG0/GT and GT/GG isomerizations are 1.90 and 9.64 kJ molK1, respectively. Experimental data obtained for the compound isolated in solid argon, krypton and xenon demonstrated that the GG0/GT energy barrier is low enough to allow an extensive conversion of the GG0 form into the GT conformer during deposition of the matrices, the extent of the conversion increasing along the series Ar!Kr!Xe. Indeed, for substrate temperatures lower than ca. 30 K, the three conformers could be trapped in both argon and krypton matrices, but, at a given temperature, the amount of GG0 form trapped in krypton is considerably smaller than in argon, while the amount of GT form increases in relation to the most stable GG form. In addition, when xenon is used, no bands due to GG0 are observed in the as-deposited spectra (TsubstrateR10 K, the minimum substrate temperature accessible to our experimental set up), indicating that when the best relaxant gas is used the GG0/GT conversion during deposition of the matrix is complete even at 10 K. Annealing of the argon and krypton matrices shows that the increase of the temperature of the matrix first promotes the GG0/GT isomerization, and only at higher temperatures the GT/GG conversion starts to occur, in consonance with the relative energy barriers associated with these two processes. The results also indicate that dimethyl sulfite exhibits conformation selective aggregation, with the most stable form, which has the highest dipole moment, aggregating more easily than the remaining experimentally relevant conformers (GT and GG0).